Women's perceived benefits of exercise during and after breast cancer treatment. - Bulmer, Sandra Minor; Howell, Jeremy; Ackerman, Louise; Fedric, Regan (Women & Health, 2012)
Empirical data support the benefits of physical activity for women who have been diagnosed with breast cancer. However, the experience of exercising during or after breast cancer treatment has not been fully documented. The purpose of the researchers in this study was to provide an in-depth description of women's experiences with exercising during or after their breast cancer treatments, specifically, their perceptions of the benefits they experienced as a result of participation in an individualized exercise program that included cardiovascular and resistance activities. Forty-five women who had been diagnosed with breast cancer within the previous two years were recruited from two oncology practices after electing to enroll in an exercise program. Data were collected between September 2006 and August 2007 through in-depth interviews at various stages in the exercise program and analyzed simultaneously using thematic analysis methods. Whether in treatment or post-treatment, women attributed psychological, physical, and social benefits to their participation in the exercise program. Participants credited the program with helping them to feel better, regain control over their bodies and their lives, manage their emotions, and prepare them to live healthfully going forward. These results provide insight into the specific ways women experience exercise during and after their breast cancer treatments.
24 citations (Crossref) [2023-10-31] Place: United States Bulmer, Sandra Minor. Department of Public Health, Southern Connecticut State University, New Haven, CT 06515, USA. bulmers1@southernct.edu
Keywords: *Adaptation; Psychological; *Breast Neoplasms/px [Psychology]; *Exercise Therapy/px [Psychology]; *Resistance Training; Adaptation; Psychological; Adult; Breast Neoplasms; Breast Neoplasms/di [Diagnosis]; Breast Neoplasms/rh [Rehabilitation]; Breast Neoplasms/th [Therapy]; Exercise Therapy; Female; Health Care Surveys; Health Services Accessibility; Humans; Interviews as Topic; Middle Aged; Perception; Physical Fitness; Qualitative Research; Questionnaires; Resistance Training; San Francisco; Social Support; Stress; Psychological; Stress; Psychological/px [Psychology]; Surveys and Questionnaires; United States; adaptive behavior; adult; article; breast cancer; breast tumor; dept.hhs; exercise; female; fitness; health care delivery; health care survey; human; interview; kinesiotherapy; mental stress; middle aged; perception; psychological aspect; psychosocial; qualitative research; questionnaire; resistance training; social support; women's health

Trends in alcohol consumption among undergraduate students at a northeastern public university, 2002-2008. - Bulmer, Sandra Minor; Irfan, Syed; Mugno, Raymond; Barton, Barbara; Ackerman, Louise (Journal of American college health : J of ACH, 2010)
OBJECTIVE: This study examined alcohol consumption patterns and trends at a public university in the Northeast from 2002 to 2008., PARTICIPANTS: Stratified random sampling was used to select undergraduate students enrolled in courses during spring semesters in 2002, 2004, 2006, and 2008., METHODS: Data were collected during regularly scheduled classes for 4 measures of alcohol consumption and 5 demographic categories using the Core Alcohol and Drug Survey., RESULTS: Four groups showed significant increases in both frequency and volume of alcohol consumption-students who were female, over 21 years of age or over, living off-campus, or performing well academically. There were no decreasing trends for any demographic group. These results differ from national college health surveys, which have shown alcohol use remaining steady during this period., CONCLUSIONS: Campus-specific trend data can provide unique perspectives and guide programming efforts. These trends suggest a need for new intervention strategies on this campus.
7 citations (Crossref) [2023-10-31] Place: United States Bulmer, Sandra Minor. Department of Public Health, Southern Connecticut State University, New Haven, Connecticut 06515, USA. bulmers1@southernct.edu
Keywords: *Alcohol Drinking/ep [Epidemiology]; *Public Sector/sn [Statistics & Numerical Data]; *Students/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Alcohol Drinking; Alcohol consumption; College; Connecticut; Data Collection; Drinking; Female; Humans; Male; Public Sector; Risk-Taking; Statistics; Nonparametric; Students; Trends; United States; Universities; Young Adult; adult; article; dept.mat; dept.pch; drinking behavior; female; high risk behavior; human; information processing; male; nonparametric test; organization and management; peer-reviewed; statistics; student; university